Application of Hybrid Algorithm in Determining the Shortest Route Between Campus Branches - Waeisul Bismi; Windu Gata; Anton .; Taufik Asra (Ultima Computing : Jurnal Sistem Komputer, 2021)
Traffic congestion in the capital city is a familiar sight for the citizens of the capital, because two-wheeled vehicle users dominate the streets of the capital city as much as 72.8 percent while four-wheeled vehicle users are 26.5 percent. And congestion has a negative impact on the activities of the various citizens of the capital city, both in terms of work and in education. Therefore, an effective solution for road users in the capital city in overcoming congestion is to find the shortest route to get to the destination quickly. The application of the Djikstra algorithm is a solution in this case by determining the shortest route from the origin to the destination in order to get to the destination faster. Therefore, the researcher conducted a case study on the way to the STMIK Nusa Mandiri Kramat 18 campus as the place of origin to the STMIK Nusa Mandiri Jatiwaringin campus as the goal by trying to apply the Djikstra algorithm as a method of finding the shortest route.